On Gaussian Fibonacci Functions with Periodicity (European Journal of Pure and Applied Mathematics, 2023)
In this work, Gaussian Fibonacci functions with the use of the (ultimately) periodicity and exponential Gaussian Fibonacci functions are also discussed. Especially, by giving a nonnegative real valued function, several exponential Gaussian Fibonacci functions are attained.
Keywords: Gaussian Fibonacci functions; Gaussian (ultimately) periodic; Fibonacci functions